Comparison of different poultry egg yolks-citrate extender with green tea (Camellia sinensis) extract addition on Sapudi ram spermatozoa quality in chilled temperature storage - Shinta Putri Quraini; Suherni Susilowati; Tjuk Imam Restiadi; Sri Chusniati (Ovozoa: Journal of Animal Reproduction, 2022)
Preservation of ram semen has an impact on the exposure of artificial conditions to the spermatozoa which was followed by overproduction of reactive oxygen species (ROS) and resulted in functional damages of spermatozoa. This study aimed to determine the effect of the combination of chicken, quail, and duck egg yolks with green tea extract (GTE) on the quality of Sapudi ram spermatozoa at 5°C storage. Ejaculates of Sapudi ram with more than 70% spermatozoa motility were divided into four groups. Semen were extended 1 : 10 in citrated-chicken egg yolk extender (control group, T0), and citrated yolk of chicken (T1), quail (T2), and duck (T3) egg added with 0.05 mg GTE per 100 mL of extender. Extended semen was kept in a tube, which was put in a beaker containing distilled water and stored in a refrigerator (5°C). Spermatozoa motility, viability, and plasma membrane integrity (PMI) were evaluated daily for five days. The results showed that GTE in duck egg yolk citrate extender could maintain the highest spermatozoa motility, viability, and PMI for five days (p <0.05). It could be concluded that the duck egg yolk citrate extender with the addition of GTE (Camellia sinensis) was beneficial for maintaining the semen of Sapudi ram spermatozoa at chilled temperatures. Further study is needed to use the extender for freezing Sapudi ram semen.